2022
DOI: 10.3390/molecules28010122
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Citrus Lemon Peel Extract and Resveratrol on Premature Ovarian Failure Rat Model: Role of iNOS/Caspase-3 Pathway

Abstract: Premature ovarian failure (POF) is described as a loss of oocytes and the absence of folliculogenesis and is considered an adverse effect of chemotherapeutic drugs, which leads to infertility. Subsequently, the existing inquiry was achieved by exploring the potential suspicious influences of lemon peel extract (LPE), and resveratrol (RES) on cyclophosphamide (CPA) induced-POF. The results showed that CPA-induced POF significantly decreased serum estradiol (E2) and progesterone levels, along with a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
0
2
1
Order By: Relevance
“…Luan et al also found that administration of CTX resulted in the loss of primordial oocytes through apoptotic pathways [ 61 ]. Although our results indicated an upregulation in apoptosis after CTX exposure, there seemed to be no significant correlation with the caspase-3 pathway, which differs from the observations of other studies [ [39] , [62] ]. We surmise that this disparity might be ascribed to the method of determining caspase-3, as another study also found that cleaved caspase-3 staining can only be observed in primary, secondary, and pre-antral follicles (except PMF) [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Luan et al also found that administration of CTX resulted in the loss of primordial oocytes through apoptotic pathways [ 61 ]. Although our results indicated an upregulation in apoptosis after CTX exposure, there seemed to be no significant correlation with the caspase-3 pathway, which differs from the observations of other studies [ [39] , [62] ]. We surmise that this disparity might be ascribed to the method of determining caspase-3, as another study also found that cleaved caspase-3 staining can only be observed in primary, secondary, and pre-antral follicles (except PMF) [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These natural products encompassed substances derived from plants to marine organisms. Among the phytochemicals, bioactive substances from plants were extensively investigated [ 27 , 30 , 32 – 37 , 39 43 , 46 , 47 , 49 52 , 63 ]. In addition, marine natural products such as tilapia skin peptides [ 38 ], oyster polypeptides [ 44 ], sea cucumber peptide [ 31 ], and coenzyme Q10 [ 45 ] were also explored.…”
Section: Resultsmentioning
confidence: 99%
“…The alleviated clinical signs in LEM-EO pretreated mice were paralleled by less distinct pathogen-induced colonic epithelial cell apoptosis. Although several investigations revealed pro-apoptotic effects of LEM in distinct cancer cells, two studies showed that the activation of caspase-3, which leads to apoptosis, is inhibited by LEM in the premature ovarian failure rat model ( Mobasher et al, 2023 ) and in human astrocytes CCF-STTG1 ( Koo et al, 2002 ), indicating that the pro- and anti-apoptotic effects of LEM are cell-type dependent. Furthermore, linalool derived from COR-EO has been shown to exert anti-apoptotic effects by the inhibition of caspase-3 and -9 attenuating ischemic injury in rodent PC12 cells ( Hosseini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%